Emerging Trends in Clinical Chemistry: The Role of Artificial Intelligence and Nanotechnology in Precision Diagnostics - Alsada, Fatima Adnan Hussien Abd; Fatale, Akram Hasan Alwan; Abdallah, Maymona Abd hammad; Aldehdar, Noor Qasim Mohammed Abed; Ftaih, Fatima Ahmed Farhan (American Journal of Biomedicine and Pharmacy, 2025)
The field of clinical chemistry is experiencing a significant transformation driven by advancements in artificial intelligence (AI) and nanotechnology, yet there remains a gap in fully integrating these technologies into routine diagnostics and personalized medicine. This review explores the intersection of AI, nanotechnology, and clinical chemistry, analyzing their roles in enhancing precision diagnostics, laboratory automation, and data-driven decision-making. By critically evaluating case studies and recent technological developments, the study finds that AI enhances data interpretation and predictive diagnostics, while nanotechnology improves sensitivity, speed, and miniaturization of diagnostic tools. Results demonstrate that AI-assisted diagnostics and nanosensors significantly reduce diagnostic errors, improve early disease detection, and support personalized healthcare solutions. However, challenges related to regulatory standards, data privacy, and ethical considerations remain obstacles to widespread implementation. The study underscores the necessity of interdisciplinary collaboration and regulatory innovation to realize the full potential of AI and nanotechnology in transforming clinical diagnostics.